Letters to Lord Byron - Minta, Stephen (Romanticism on the Net, 2007)
AbstractA number of unpublished letters among the papers of the London Greek Committee in the National Library of Greece throw particular light on the significant period, in 1823, when Byron was considering how best he might contribute to the cause of Greek independence. The letters discussed here are: (1) Alexandros Mavrokordatos from Tripolitza, to Byron in Genoa, dated 2/14 July 1823 (vol. v, fo. J) ; (2) James Hamilton Browne from Tripolitza, to Byron in Kefalonia, dated 13 September 1823 (vol. v, fo. H); and (3) Edward John Trelawny from Tripolitza, to Byron in Kefalonia, dated 14 September 1823 (vol. v, fo. I). Browne’s letter contained two interesting enclosures, which are also considered here: (4) ‘Substance of a conversation held with Colococtroni in his palace’ (vol. v, fo. K), and (5) ‘Substance of a conversation which took place with the Officers of Mavrocordato, who remain here’ (vol. v, fol. L). I also look briefly at the following letters: (6) Spiridion Trikoupis from Hydra, to Byron in Kefalonia, 15/27 August 1823 (vol. v, fol. C); (7) Andreas Louriotis from Hydra, to Byron in Kefalonia, 15/27 August 1823 (vol. v. fol. D); and (8) Mavrokordatos from Hydra, to Byron in Kefalonia, 15/27 August 1823 (vol. v, fol. E).